Gestão de Processos e Gestão de Riscos para Enfrentar Enchentes no Estado do Rio Grande do Sul: Uma pesquisa de caráter bibliográfico - Magni, Jenifer (2023)
This study aims to investigate and identify effective process management strategies that can be applied to enhance flood response in the state of Rio Grande do Sul, with a focus on risk management as an integral part of this process. Regarding the methodological aspects, the research was conducted through exploratory research with technical procedures of bibliographical and documentary research from official websites. The main results include the implementation of a protocol that integrates process management and its phases, using some information from the Sendai Framework, an international agreement for disaster management by the United Nations, valid until 2030. With the comparison and integration of the data proposed and obtained, the conclusion is to take advantage of the process techniques when applied in flood-type events, as well as risk management, to obtain the guarantee of reduction of these disasters as a result of the current situation that the state has been facing with predictability and prognosis